Pios hydrogen fuel cell tricycle - Weigl, Joerg (Elsevier, 2005)
The Pios fuel cell tricycle was designed and built to make hydrogen and fuel cell technology visible and cycleable for the public and the media. However, with its impressive cruising range of about 800 km, it is much more than a demonstration vehicle for fairs. The tricycle is allowed to use the roads as a cycle with an additional electrical engine or as a small motor bike up to 45 km/hr without restriction. The vehicle is built with components that are available at the still limited market for hydrogen technology and electric bicycle parts. The hydrogen tank for compressed hydrogen can be refilled from standard hydrogen bottles to a pressure up to ~ 180 bar. The fuel cell tricycle is a completely integrated system of a fuel cell, peripheral devices, and hydrogen supply. It is connected to an electrical engine, over a DC-DC-converter, an energy buffer (lithium polymer accumulator) and a motor controller (four-quadrant-synchronous-three-phase-motor controller, which means forward and backward driving and regenerative braking).